Influence of Sex in the Molecular Characteristics and Outcomes of Malignant Tumors - Araujo, Jhajaira M.; Rosas, Gina; Belmar-López, Carolina; Raez, Luis E.; Rolfo, Christian D.; Schwarz, Luis J.; Infante-Huaytalla, Ulises; Paez, Kevin J.; García, Luis R.; Alvarado, Hober; Ramos, Fany P.; Delgado-Espinoza, Sheyla S.; et al. (Frontiers in Oncology, 2021)
Background Sex is frequently underestimated as a prognostic biomarker in cancer. In this study, we evaluated a large cohort of patients and public datasets to determine the influence of gender on clinical outcome, mutational status, and activation of immune pathways in several cancer types Method and Patients We analyzed a twenty-year period cohort of 13,619 patients bearing cancers not related to sex affiliated to Oncosalud-AUNA (Peru). Hazard ratios (HR) for death were estimated for female vs. male patients for each cancer type and then pooled in a meta-analysis to obtain an overall HR. On the other hand, the mutational status of the main actionable genes in melanoma, colorectal cancer, and lung cancer were compared between sexes. Finally, we conducted a GSEA analysis of publicly available data to assess differences in immune processes between genders in melanoma (MEL), gastric adenocarcinoma (GAC), head and neck cancer (HNC), colon cancer (CC), liver cancer (LC), pancreas cancer (PC), thyroid cancer (TC) and clear renal cell carcinoma (CCRCC). Results Overall, women had a decreased risk of death (HR=0.73, IC95%:8%-42%) with improved overall survival (OS) in HNC, leukemia, lung cancer (LC), lymphoma, MEL, multiple myeloma (MM), and non-melanoma skin cancer. Regarding to differences in actionable mutations, only differences in EGFR alterations were seen (27.7% for men vs 34.4% for women, p=0.035)). The number of immune processes differentially activated was higher in female tumors in HNC, LC, CC, GAC, MEL, PC and TC, and included cellular process, response to stimulus, immune system development, immune response, multi-organism process, localization of immune cells and activation of immune response. Only CCRCC showed a higher activation of immune pathways in males. Conclusions: An improved survival and enrichment of EGFR alterations in female patients was seen in our cohort as well as a strong activation of immune pathways. Enhancement of the immune response in female patients is a phenomenon that should be better explored to improve the efficacy of immunotherapy.